Environmental and Behavioral Determinants of Tuberculosis: A Narrative Review - Afrianto, Indra (Yayasan Sinergi Kawula Muda, 2024)
Tuberculosis (TB) remains a major public health challenge, driven by a complex interaction of environmental and behavioral factors. This study examines how air pollution, poor sanitation, and urban overcrowding contribute to TB prevalence, alongside behavioral determinants such as smoking and treatment adherence. A systematic review was conducted, analyzing peer-reviewed studies from databases including PubMed, Scopus, and Google Scholar. The findings indicate that fine particulate matter (PM2.5), biomass fuel use, and inadequate ventilation significantly increase TB risk, while smoking and stigma-related delays in treatment further exacerbate transmission. Socioeconomic inequalities were also found to play a critical role in limiting healthcare access for vulnerable populations. Mitigation strategies should include stricter air quality regulations, improved housing infrastructure, and expanded public health education programs to encourage early diagnosis and adherence to treatment. Successful TB control models from countries like Brazil demonstrate the effectiveness of integrating community engagement with robust healthcare policies. Future research should explore the intersection of TB with climate change and antimicrobial resistance to develop long-term, sustainable solutions. Addressing TB requires a multidisciplinary approach, combining environmental policies, public health initiatives, and community-driven interventions to reduce global incidence rates.